Healing beyond borders: intellectual property, traditional knowledge, and the future of Unani medicine - Ashrafi, Raina; Shakeel, Tahniyat; Anas, Mohammad (International Journal of Research in Medical Sciences, 2025)
There are unique issues and opportunities related to intellectual property in the development of modern Unani medicine. With increasing global interest in traditional and herbal medicines, Unani pharmaceutical companies face the challenge of continuously improving their products while staying true to traditional knowledge. Therefore, patent protection and compulsory licensing are essential in this transition process, balancing invention rights and public health concerns related to Unani treatments. Patents encourage innovation by providing exclusive rights for specific solutions and techniques, often attracting venture capital for development. However, these rights can also limit access, especially in poor regions where traditional cures are most needed. Compulsory licensing offers a viable alternative, allowing governments or authorized bodies to produce patented medicines without the patent holder’s consent in certain situations, such as in the public interest. In Unani medicine, compulsory licensing may be particularly useful for regulating patent-holding companies and ensuring they respond to societal needs by providing necessary treatments. This paper explores how patents and compulsory licensing influence Unani pharmaceuticals, focusing on how policy makers shape and enforce intellectual property rules to manage commercialization, access, and international market growth. It is crucial to balance the use of traditional Unani medicine to make it a practical, culturally sensitive, and affordable healthcare option for the global community.